Process Advantages of Direct CO2 to Methanol Synthesis - Marlin, Dana S.; Sarron, Emeric; Sigurbjörnsson, Ómar (Frontiers in Chemistry, 2018)
Developing a laboratory scale or pilot scale chemical process into industrial scale is not trivial. The direct conversion of CO2 to methanol, and concomitant production of hydrogen from water electrolysis on large scale, are no exception. However, when successful, there are certain benefits to this process over the conventional process for producing methanol, both economic and environmental. In this article, we highlight some aspects that are unique to the process of converting pure CO2 to methanol. Starting from pure CO2 and a separate pure source of H2, rather than a mixture of CO, CO2 and H2 as is the case with syngas, simplifies the chemistry, and therefore also changes the reaction and purification processes from conventional methanol producing industrial plants. At the core of the advantages is that the reaction impurities are essentially limited to only water and dissolved CO2 in the crude methanol. In this paper we focus on several aspects of the process that direct conversion of CO2 to methanol enjoys over existing methods from conventional syngas. In particular, we discuss processes for removing CO2 from a methanol synthesis intermediate product stream by way of a stripper unit in an overhead stream of a distillation column, as well as aspects of a split tower design for the distillation column with an integrated vapo-condenser and optionally also featuring mechanical vapor re-compression. Lastly, we highlight some differences in reactor design for the present system over those used in conventional plants.